Acculturation of Marriage: Bugis and Dayak Tribes in Lampuyang Samuda Village, East Kotawaringin - Normery Andani; Muhammad Husni; Suryanti (Journal of Islamic History, 2026)
This study attempts to evaluate the process and forms of cultural acculturation in marriages between the Bugis and Dayak tribes in Lampuyang Village, Teluk Sampit District, East Kotawaringin Regency. The focus of the research is targeted at how these two cultural traditions interact and adapt in marriage rituals within a multiethnic community. This study combines a qualitative approach employing ethnographic methodologies reinforced with a historical viewpoint to trace the background of the meeting of Bugis and Dayak civilizations in the region. Data were obtained from field observations, in-depth interviews with traditional leaders, village officials, bridal couples, and documentation studie. The results show that Bugis and Dayak marriages in Lampuyang Village are the result of a selective and dialogical acculturation process. Traditional elements from both tribes are maintained but are adjusted through family agreements and the influence of dominant Islamic religious values. This acculturation does not lead to the elimination of cultural identity, but rather forms a contextual and adaptive pattern of integration. Thus, interethnic marriages in Lampuyang Village can be understood as a space for cultural negotiation as well as a means of social integration in a multiethnic society. REFERENCES Arifin, RH, & Saleh, M. (2022). THE SYMBOLIC MEANING OF THE MAPACCI PROCESSION AT THE BUGIS PANGKEP TRADITIONAL WEDDING IN THE PA'BUNDUKANG VILLAGE, PANGKEP DISTRICT. Berry, J. W. (2005). Acculturation: Living successfully in two cultures. International Journal of Intercultural Relations, Special Issue: Conflict, negotiation, and mediation across cultures: highlights from the fourth biennial conference of the International Academy for Intercultural Research, 29(6), 697–712. https://doi.org/10.1016/j.ijintrel.2005.07.013 Dewi, M., & Riyanto, ED (2022). Assimilation and Acculturation of Punjungan Culture in the Wedding Procession of Transmigrant Communities in Bumi Minangkabau. Sang Pencerah: Scientific Journal of Muhammadiyah University of Buton, 8(2), 444–457. https://doi.org/10.35326/pencerah.v8i2.1928 Drouhot, L. G., & Nee, V. (2019). Assimilation and the Second Generation in Europe and America: Blending and Segregating SocialDynamics Between Immigrants and Natives. Annual Review of Sociology, 45(1), 177–199. https://doi.org/10.1146/annurev-soc-073117-041335 Ekawati, NA, Erawati, D., & Suryanti. (2022). Migration of the Bugis in Bapeang Village of East Kotawaringin, 1977-2020 (Historical Review of Social Change Perspective). Syams: Journal of Islamic Studies, 3(2), 115–128. https://doi.org/10.23971/js.v3i2.5831 Endraswara, S. (2006). Techniques and theories of cultural research: Ideology, epistemology, and applications. Widyatama Library. Halim, A. (2020). Journal of Social and Religious Research. 5(1). Hisyam, CJ (2021). Indonesian Socio-Cultural System. Bumi Aksara. King, V. T. (2013). Borneo and Beyond: Reflections on Borneo Studies, Anthropology and the Social Sciences. https://repository.ubd.edu.bn/handle/123456789/3672 Koentjaraningrat. (2000). Introduction to Anthropology . Jakarta: Rineka Cipta Kuntowijoyo. (2013). Introduction to Historical Science. Tiara Wacana. Noor, AS, & Khosmas, FY (2021). CHANGES IN TRADITIONAL WEDDING VALUES OF THE KANAYATN DAYAK TRIBE IN SADANIANG DISTRICT, MEMPAWAH REGENCY. Nuruddaroini, MAS (2019). WEDDING CUSTOMS OF THE BANJAR AND BUGIS TRIBES. Social Culture, 16(1), 25. https://doi.org/10.24014/sb.v16i1.6960 Lampuyang Village and Sub-district Profile. (2025). Lampuyang Village Profile, Teluk Sampit District, East Kotawaringin Regency . Lampuyang Village Government. Environmental Science Study Program, Faculty of Science and Technology, PGRI University of Palembang and Population Research Center, National Research and Innovation Agency (BRIN), & Armansyah, A. (2022). The Impact of Population Migration on the Acculturation of Traditions Among the Population. Geodika: Journal of Geographical Science and Education Studies, 6(1), 25–34. https://doi.org/10.29408/geodika.v6i1.4463 Putri, N.A., Saiban, K., Sunarjo, S., & Laila, K. (2021). The Position of Panaik Money as a Marriage Requirement in Bugis Customs Based on Islamic Law. Bhirawa Law Journal, 2(1), 33–44. https://doi.org/10.26905/blj.v2i1.5852 Spradley, JP (2006). Ethnographic techniques . Yogyakarta: Tiara Wacana. Sudirman, M. (2019). THE “MAPPASIKARAWA” TRADITION IN BUGIS TRADITIONAL WEDDINGS. 5. Suryanti, S., Mz, I., & Rahmah, ST (2020). History of the Bugis-Makassar Diaspora in Central Kalimantan. Rihlah: Journal of History and Culture, 8(2), 100–112. https://doi.org/10.24252/rihlah.v8i2.15707 Widen, K. (2023). Dayak People and Their Culture. Journal of Social Sciences, Politics and Government, 1 2 (2), 207–218. https://doi.org/10.37304/jispar.v12i2.9834 Interview with Village Head, Banjar Tribe in Lampuyang Village, 2025. Interview with the Head of RT 5, Bugis Tribe in Lampuyang Village, 2025. Interview with DKA Dayak Teluk-Sampit, Bugis Tribe in Lampuyang Village, 2025. Interview with a Bride and Groom, Bugis and Dayak Tribes in Lampuyang Village, 2025. Interview with the parents of the bridal couple, in Lampuyang Village, 2025.